2003
DOI: 10.1023/a:1021639016300
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ASY, also designated Nogo, RTN-X, or RTN4, is a reticulon family protein containing two transmembrane domains and a C-terminal double lysine endoplasmic reticulum (ER) retrieval motif. Three protein variants are synthesized from the cognate mRNAs produced by alternative splicing, and are expressed in almost all tissues, localizing predominantly in the ER. The ASY protein induces apoptosis in various cancer cells when overexpressed, whereas normal cells are relatively resistant to ASY-dependent apoptosis. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Gene expression profiling therefore demonstrated that FASN inhibition induces down-regulation of genes related to cell proliferation, cell adhesion, migration, and invasion, as well as production of arachidonic acid and androgen hormones. Furthermore, in Table S2, up-regulation of genes related to induction of apoptosis, including thrombospondin 1 (THBS1), ras homolog gene family, member B (RHOB), pleckstrin homology-like domain, family A, member 2 (PHLDA2), and reticulon 4 (RTN4) [35]–[38], was observed, which supported the previous findings that FASN inhibition induces apoptosis [3], [5].…”
Section: Resultssupporting
confidence: 82%
“…Gene expression profiling therefore demonstrated that FASN inhibition induces down-regulation of genes related to cell proliferation, cell adhesion, migration, and invasion, as well as production of arachidonic acid and androgen hormones. Furthermore, in Table S2, up-regulation of genes related to induction of apoptosis, including thrombospondin 1 (THBS1), ras homolog gene family, member B (RHOB), pleckstrin homology-like domain, family A, member 2 (PHLDA2), and reticulon 4 (RTN4) [35]–[38], was observed, which supported the previous findings that FASN inhibition induces apoptosis [3], [5].…”
Section: Resultssupporting
confidence: 82%
“…We observed another unexpected integration in the intronic region of RTN4 only in a normal tissue, though its integration allele fraction was only 2.35%. RTN4 has been demonstrated to induce apoptosis in cancer cells but play an opposite role in normal cells [32]. Similarly, we found an unexpected integration in the intronic regions of EWSR1 only in normal tissue, with an integration allele fraction of only 3.13%.…”
Section: Discussionsupporting
confidence: 71%
“…cyp19a1a was proposed as the major gene for female determination in zebrafish [56]. Additional overexpressed genes in females such as rtn4ip1 , impa1, socs7 and zp3 are involved in anti-apoptotic activity, embryonic development and fertility, prolactin and Jak-STAT signaling pathway and ovary development, respectively [6770]. …”
Section: Discussionmentioning
confidence: 99%